Understanding a Necessary Relationship between Individual and Society in Iqbal's Concept of the Self - Abdul Rahim, Adibah (2011)
The concept of self is the most important views to be discussed because it is the central idea of Iqbal’s philosophy on which the rest of his thought-structure is based. For Iqbal, understanding the nature of the self is essential for an understanding of the nature of society and the principle of its growth. Self, according to Iqbal, is an active and creative force in which a person should strive towards the achievement of a rich personality as well as participate in the affairs of the universe to suit his highest position as the vicegerent of God on earth. This paper attempts to discuss the nature of the self as expounded by Iqbal and how the self grows into a strong and powerful personality. Iqbal does not only preach self-realization by individuals, but his idea also prescribes suppression of individualism, which precludes any collective and concerted effort. Iqbal has recognized a necessary relationship between the individual and society. He sees society as a must for the proper growth and development of human and it is only in society that man can achieve self-realization. It is at this juncture that this paper also tries to discuss the nature of mutual relationship between the individual and society wherein man lives, moves, and exists.